A TRANSLATION ANALYSIS OF INDONESIAN SONG LYRICS INTO ENGLISH - Niswatin Nurul Hidayati (JP : JURNAL PENDIDIKAN, 2020)
Abstract: This research aimed to describe the translation method used by Emma Heesters in translating two Andmesh Kamaleng’s song lyrics, Cinta Luar Biasa and Hanya Rindu into Incredible Love and Just Missing You whether she used translation method emphasizing on the source or target language. Besides, the author also intended to analyze the reason why such translation method was used. The author used qualitative research as the method and case study as the design. The objects of this research were song lyrics of Cinta Luar Biasa and Hanya Rindu, also the translated version by Emma Heesters. In collecting the data, documentation technique was used, in which the author collected both Indonesian and English version of the song lyrics. The author analyzed the data by using Newmark’s theory. The result showed that the mostly the translation method used was emphasizing mostly on the target language, even some part of the song lyrics were emphasizing on the source language. Then, the reason why Emma Heesters tended to use the translation method emphasizing on the target language because she had to manage the translation could be match with the intonation or tone of the song. Besides, the gender of the singer also caused this because some parts of the lyrics were modified so that they were match with the female singer, while the original version was sung by a male singer.